ẢNH HƯỞNG CỦA MƯA ĐẦU MÙA TỚI ĐỘ DÀY QUANG HỌC SOL KHÍ TẠI BẠC LIÊU - Thanh, Pham Xuan (Vietnam Journal of Earth Sciences, 2011)
Impact of rainfall in summer onseting monsoon on aerosol optical depth in Bac Lieu Impact of rainfall in summer onseting monsoon on the Aerosol Optical Depth (hereafter AOD) and size distribution of aerosols elements were evaluated in the case of the rainy season in 2003 based on hourly rainfall data in Bac Lieu and AOD data from Aerosol Robotic Network (AERONET). First, we specify the onset of summer monsoon over the Southern Vietnam and the rainy days in the early rainfall season is also detected in 2003 from Bac Lieu rain gauge data. After that, effect of early season rainfall in 2003 on AOD and size distribution is evaluated by the decrease of AOD at 500nm and the change of Angstrom parameters. Results show that the onset of the summer monsoon over the Southern Vietnam in 2003 is 4-May. At that time, we detected 3 rainy days from Bac Lieu rain gauge station data, it is 1, 3 and 4 with the rainfall is 4, 7.5 and 5.5, respectively. The rains of early season rainfall in 2003 significantly reduced the aerosol optical depth. After 3 rainy days, AOD at 500nm wavelength decreased from 0.4 to 0.1. The rain in early season rainfall also changed size distribution of aerosols elements in the atmosphere. The aerosols elements have large size is swept away by the first rainy day. The β decreased from 0.23 (30 April) to 0.07 (3 May) and 0.04 (5 May). The difference of AOD at 500nm between the first month of rainfall season and the last month of dry season in period 2003 - 2009 is 0.025. The AOD average rainfall season and dry season is 0.29 and 0.19, respectively. The AOD in 500nm average of four dry months (Dec, Jan, Feb and Mar) is 0.29 and of rainy months (Jun, Jul, Aug, and Sep) is 0.19.